Potential Increases in Willingness to be Vaccinated due to the Introduction of a Combined Influenza/COVID-19 Vaccine - Matt Jenkins; Constantina Boikos; Joshua Coulter; Dr Verna L Welch; Cherie Stuntz; Verna Welch (International Journal of Infectious Diseases)
Introduction: To estimate potential increases in willingness to be vaccinated (WTV) to prevent COVID-19 and influenza in the United States (US) after introducing a combined Influenza/COVID-19 vaccine. Methods: US adults were surveyed to assess WTV with a combination Influenza/COVID-19 vaccine, separate Influenza and COVID-19 vaccines, or COVID-19 or influenza vaccine alone under three combination vaccine scenarios: (1) similar adverse event (AE) rates, (2) 10% increase in both localized and systemic AEs, (3) 20% increase in localized and 25% increase in systemic AEs. All scenarios assumed a combination vaccine with equivalent efficacy to current vaccines. Increases in WTV with the combination vaccine were calculated. Results: Among 5,009 participants, 50% were female and 39%, 30%, and 31% were aged 18-34, 35-49, and 50-64 years, respectively. The majority (64%) were white or Caucasian. Current vaccination rates were 4% for COVID-19 only, 18% for influenza only, 11% for both vaccines at different visits, and 11% for both vaccines at one visit. 56% had received neither vaccine in the past year. In Scenario 1 (similar AEs), influenza and COVID-19 vaccination rates may increase by up to 26 and 34 percentage points, respectively. Scenario 2 (10% increase in both localized and systemic AEs) indicated increases of up to 20 and 25 percentage points, respectively. Scenario 3 indicated increases of up to 15 and 19 percentage points, respectively. Discussion: Potential increases in WTV include both people adding one vaccine to what they already receive as well as increases in WTV among those who chose not to be vaccinated in the past year. Between 23% and 41% of respondents who had received no vaccine indicated WTV if the combination vaccine were available. Conclusion: The introduction of a combination Influenza/COVID-19 vaccine may increase WTV against COVID-19 and influenza even when efficacy of each component is non-inferior to current vaccines.